Fire barrier material and battery pack using the same

CN122893192APending Publication Date: 2026-10-09MAFTEC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202680002300.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-01-31
Filing Date
2026-01-26
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]车辆中使用的这种电池单元主要使用能够实现高容量和高输出的锂离子二次电池,但可能会因碰撞事故、电池劣化或异常充电引起的热失控而导致起火

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122893192A_ABST
    Figure CN122893192A_ABST
Patent Text Reader

Abstract

The fire stopping material of the present application includes: an inorganic fiber nonwoven fabric; and a thickness inhibitor impregnated in the inorganic fiber nonwoven fabric; the inorganic fiber nonwoven fabric is kept in a compressed state in the thickness direction by the thickness inhibitor. The inorganic fiber nonwoven fabric recovers to a thickness of 60% or more of the thickness before the thickness inhibitor was impregnated by the disappearance of the thickness inhibitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a fire-retardant material and a battery pack using the fire-retardant material. Background Technology

[0002] In electric vehicles or hybrid vehicles, a battery pack (also called a battery module) is a power source for the electric motor that drives the vehicle. It consists of multiple cells (also called battery units) connected together.

[0003] The battery cells used in these vehicles primarily employ high-capacity, high-output lithium-ion rechargeable batteries, but they are susceptible to fire due to thermal runaway caused by collisions, battery degradation, or abnormal charging. Extinguishing a battery cell that has experienced thermal runaway is difficult. To prevent a chain reaction of thermal runaway and protect occupants, fire-retardant materials are required within the battery pack. To prevent the spread of fire due to heat diffusion to the outside of the battery pack, the fire-retardant material needs to be heat-insulating. For high heat insulation, the thicker the fire-retardant material, the better. On the other hand, due to space constraints, the fire-retardant material mounted within the battery pack must be as thin as possible. Because the thinner the material, the lower its heat insulation, ultimately, there is an inverse relationship between heat insulation and load-bearing capacity.

[0004] Patent document 1 discloses an inorganic fiber composite material, characterized in that it has a sheet-like inorganic fiber molded body, and at least one side of the inorganic fiber molded body has a particle impact resistant layer, which has specific particle impact resistance.

[0005] Patent Document 2 discloses a heat transfer inhibition sheet comprising: at least one of a first inorganic fiber having a glass transition temperature of 800°C or less and a first inorganic particle having a glass transition temperature of 800°C or less; a second inorganic fiber having a glass transition temperature of 1000°C or more; a second inorganic particle having a glass transition temperature of 800°C or more; and an organic adhesive.

[0006] Patent document 3 discloses a laminate comprising: a layer (A) integrally formed of a thermoplastic resin composition (X) and an inorganic fiber (Y); and a layer (B) having a thermal conductivity in the thickness direction higher than that of layer (A); the thermoplastic resin composition (X) comprises a thermoplastic resin (a) and a thermally expanding flame retardant (b1).

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: International Publication 2024 / 034628

[0010] Patent Document 2: International Publication 2023 / 127904

[0011] Patent Document 3: International Publication 2024 / 085233 Summary of the Invention

[0012] The problem that the invention aims to solve

[0013] To ensure the inorganic fiber composite material described in Patent Document 1 has sufficient thermal insulation properties, it is necessary to increase the basis weight of the inorganic fiber molded body, which will lead to an increase in the thickness of the inorganic fiber molded body. If the thickness of the inorganic fiber molded body is large, its load-bearing capacity will be poor.

[0014] Patent document 2 describes a technique in which an inorganic binder or resin is incorporated into the inorganic fibers of an inorganic fiber molded body to process a relatively thin heat transfer suppressing sheet. However, since the inorganic binder does not disappear upon heating, the binding force of the inorganic binder on the inorganic fibers does not decrease even when the inorganic fiber molded body is heated, and the inorganic fiber molded body maintains its thinness. If the thickness of the inorganic fiber molded body is thin, the thermal insulation performance becomes lower.

[0015] In the technology described in Patent Document 3, the thermally expandable substance contained in the molded body comprising a thermoplastic resin composition (X) and inorganic fibers (Y) expands during flame retardation, thereby increasing the thickness and thus achieving a heat insulation effect. On the other hand, from the viewpoint of the dispersion of the thermally expandable substance or the control of its expansion, it is difficult to reliably and uniformly increase the thickness of the molded body.

[0016] One of the issues to be addressed in this disclosure is to provide a fire-retardant material with load-bearing and heat-insulating properties, and a battery pack having the fire-retardant material.

[0017] Technical solutions for solving the problem

[0018] This disclosure includes, for example, the following topics.

[0019] Option 1.

[0020] A fire-retardant material comprising: an inorganic fiber nonwoven fabric; and

[0021] Thickness inhibitor, impregnated in the inorganic fiber nonwoven fabric; The inorganic fiber nonwoven fabric is kept in a compressed state in the thickness direction by the thickness inhibitor. The inorganic fiber nonwoven fabric recovers to more than 60% of its original thickness before the thickness inhibitor was impregnated by the disappearance of the thickness inhibitor.

[0022] Option 2.

[0023] According to the fire-retardant material described in Scheme 1, the inorganic fiber nonwoven fabric is a needle-punched blanket containing alumina / silica fibers.

[0024] Option 3.

[0025] According to the fire-retardant material of Scheme 1, the thickness inhibitor comprises a thermoplastic resin.

[0026] Option 4.

[0027] According to the fire-retardant material of Scheme 3, the thickness inhibitor comprises a flame retardant.

[0028] Option 5.

[0029] According to the fire-retardant material described in Scheme 1, the basis weight of the inorganic fiber nonwoven fabric is between 400 and 1400 g / m³. 2 Within the range.

[0030] Option 6.

[0031] According to the fire-retardant material described in Scheme 1, the GBD of the inorganic fiber nonwoven fabric in the compressed state is 0.47 g / cm³. 3 the following.

[0032] Option 7.

[0033] A battery pack comprising: a plurality of battery cells; a battery housing for accommodating the plurality of battery cells; and a fire-retardant material as described in any one of embodiments 1 to 6, accommodating within the battery housing. Attached Figure Description

[0034] Figure 1 This is a perspective view of the fire-retardant material used in the implementation method.

[0035] Figure 2 This is a schematic diagram of the battery pack in the implementation method.

[0036] Figure 3 This is a graph showing the temperature change of a stainless steel (SUS) plate over time when heated in a burner and when samples of various flame-retardant materials are used.

[0037] Figure 4 It means Figure 3 The graph shows the temperature changes of SUS plates over time when samples of various fire-retardant materials are used. Detailed Implementation

[0038] In this specification, unless otherwise expressly stated in this specification or clearly contradicted in the context, the singular form is considered to include both the singular and the plural.

[0039] In this specification, "comprising" also includes the concepts of "substantially consisting only of" and "consisting only of".

[0040] In the numerical ranges described in stages in this specification, the upper or lower limit of a certain stage's numerical range can be arbitrarily combined with the upper or lower limits of the numerical ranges of other stages. Furthermore, the upper or lower limit of the numerical range described in this specification can also be replaced with the values ​​shown in the embodiments or values ​​uniquely derived from the embodiments. Moreover, in this specification, numerical values ​​connected by "~" refer to a numerical range including the values ​​before and after "~" as both the lower and upper limits.

[0041] The embodiments included in this disclosure will be further described below. It should be noted that the embodiments described below illustrate an example of a representative embodiment of this disclosure and are not intended to limit the scope of the invention.

[0042] This disclosure provides a fire-retardant material comprising: an inorganic fiber nonwoven fabric; and a thickness inhibitor impregnated in the inorganic fiber nonwoven fabric; the inorganic fiber nonwoven fabric is kept in a compressed state in the thickness direction by the thickness inhibitor, and the inorganic fiber nonwoven fabric recovers to a thickness of more than 60% of its thickness before the thickness inhibitor was impregnated when the thickness inhibitor disappears.

[0043] Inorganic fiber nonwoven fabric

[0044] Inorganic fiber nonwovens are sheet-like assemblages of fibers with a specified thickness, including, for example, inorganic fiber blankets (also known as “blankets”) or fabricated mats. Inorganic fiber nonwovens are elastic (cushioning), and therefore, under compression, they exhibit a rebound force that seeks to return to their original thickness.

[0045] The preferred inorganic fiber nonwoven fabric is a needle-punched blanket. A needle-punched blanket is an inorganic fiber nonwoven fabric that has undergone needle-punching treatment. Through needle-punching treatment, not only can a strong inorganic fiber nonwoven fabric be formed by the inorganic fibers constituting the inorganic fiber nonwoven fabric intertwining with each other, but the thickness of the inorganic fiber nonwoven fabric can also be adjusted.

[0046] When the inorganic fiber nonwoven fabric is a needle-punched blanket, it has multiple needle marks, i.e., multiple recesses. The needle marks can be through holes that extend along the thickness direction of the inorganic fiber nonwoven fabric, or they can be non-through holes.

[0047] <Material>

[0048] The inorganic fibers constituting the inorganic fiber nonwoven fabric are not particularly limited, and for example, ceramic fibers, biosoluble fibers (alkaline earth silicate fibers), rock wool, basalt fibers, potassium titanate fibers, calcium silicate fibers, glass fibers, etc., can be used. Furthermore, examples of ceramic fibers include single or composite fibers such as silica, alumina, alumina / silica, zirconium oxide, spinel, titanium dioxide, and calcium oxide. Among these, alumina / silica fibers are preferred, and crystalline alumina / silica fibers are particularly preferred. When the inorganic fiber is alumina / silica fiber, the composition ratio (mass ratio) of alumina / silica is preferably in the range of 60 / 40 to 98 / 2, more preferably in the range of 65 / 35 to 95 / 5, and most preferably in the range of 70 / 30 to 80 / 20.

[0049] <Average fiber length>

[0050] The inorganic fiber is preferably 1.0 mm or more, more preferably 2.0 mm or more, and even more preferably 3.0 mm or more in average fiber length. Furthermore, there is no particular upper limit, but 3.0 × 10⁻⁶ is preferred. 3 mm or less, more preferably 1.0 × 10 mm. 3 Less than mm. It should be noted that the average fiber length of inorganic fibers is the average value of 300 fibers measured by microscopic observation.

[0051] <Average fiber diameter>

[0052] The average fiber diameter of the inorganic fiber is preferably 3 μm to 15 μm, and particularly preferably 5 μm to 10 μm. It should be noted that the average fiber diameter is the average value of 100 fibers measured by microscopic observation.

[0053] <Base Weight>

[0054] The preferred basis weight (mass per unit area) of inorganic fiber nonwoven fabric is 1400 g / m². 2 Below. If the basis weight is set within the above range, the thickness of the inorganic fiber nonwoven fabric can be suppressed, enabling the manufacture of a fire-retardant material with improved mounting properties. This fire-retardant material can be accommodated in a limited space, such as above a battery cell or between battery cells.

[0055] Furthermore, there is no particular limitation on the lower limit of the basis weight of inorganic fiber nonwoven fabrics, but 400 g / m² is preferred. 2The above applies. If the basis weight is set within the above range, then in terms of fiber content per unit area, i.e., thickness, it is possible to manufacture fire-retardant materials with improved fire-retardant properties (especially thermal insulation).

[0056] From the perspective of balancing the fire-retardant properties and thermal insulation, the basis weight of inorganic fiber nonwoven fabric is preferably 400–1400 g / m³. 2 .

[0057] <Bulk density>

[0058] The preferred bulk density of inorganic fiber nonwoven fabric is 0.100 g / cm³. 3 The above, more preferably 0.125 g / cm³ 3 The above, especially preferred, is 0.130 g / cm³. 3 above.

[0059] Furthermore, there is no particular upper limit to the bulk density, but it is preferably 0.200 g / cm³. 3 The preferred value is 0.190 g / cm³. 3 The following is particularly preferred: 0.180 g / cm³ 3 the following.

[0060] If the bulk density is within the above range, the amount of fiber per unit volume is sufficient, thus enabling the manufacture of fire-retardant materials with improved fire-retardant properties (especially thermal insulation).

[0061] <Thickness>

[0062] The thickness of the inorganic fiber nonwoven fabric is preferably 3.00 mm to 10.0 mm.

[0063] The thickness of inorganic fiber nonwoven fabrics can be measured, for example, by the measurement method shown in the following examples.

[0064] Inorganic fiber nonwoven fabrics can be manufactured, for example, by the methods disclosed in paragraphs

[0043] to

[0064] of International Publication No. 2024 / 034628.

[0065] Thickness inhibitor

[0066] Thickness inhibitors are impregnated in inorganic fiber nonwoven fabrics to bind the inorganic fibers within the fabric and suppress its thickness, i.e., the thickness of the flame-retardant material. Examples of thickness inhibitors include thermoplastic resins, flame retardants, or both, but are not limited to these.

[0067] The thickness inhibitor preferably comprises a thermoplastic resin. Thermoplastic resin melts upon heating, thus binding the inorganic fibers in the inorganic fiber nonwoven fabric under normal conditions and releasing the inorganic fibers from the binding during heating such as thermal runaway, allowing the fire-retardant material to expand or recover. Compared to inorganic binders that do not disappear or soften upon heating, thermoplastic resin has advantages in terms of the expansion or recovery of fire-retardant materials.

[0068] The thickness inhibitor is preferably a thermoplastic resin with low viscosity when impregnated into the inorganic fibers constituting the inorganic fiber nonwoven fabric. By using a thermoplastic resin with this property, the thermoplastic resin can be more uniformly impregnated into the entire inorganic fiber nonwoven fabric.

[0069] There are no particular limitations on thermoplastic resins, but examples include: polyamide, polyurethane, ethylene-vinyl acetate (EVA), phenoxy resins, polyolefins, polycarbonate, polyvinyl chloride (PVC), and combinations of two or more of them. For example, polyamide is preferred from the viewpoint of heat resistance and strength, while polyolefins (e.g., polyethylene, polypropylene) are preferred from the viewpoint of cost and moldability.

[0070] Flame retardants prevent or inhibit the spread of fire and improve the thermal insulation of fire-retardant materials. Thickness inhibitors may or may not contain flame retardants, but are preferably present. Flame retardants are broadly classified into halogen-based and non-halogen-based flame retardants, with non-halogen-based flame retardants being preferred. Examples of non-halogen-based flame retardants include: phosphorus-based flame retardants (phosphate esters, ammonium polyphosphate, etc.), metal hydroxides (magnesium hydroxide, etc.), and polytetrafluoroethylene (PTFE).

[0071] The content of thickness inhibitors in fire-retardant materials (when there are two or more thickness inhibitors, it is the total amount) is not particularly limited, for example, it is 60 to 300 by mass relative to the inorganic fiber nonwoven fabric.

[0072] The content of thermoplastic resin (or the total amount when there are two or more types of thermoplastic resin) in fire-retardant materials is not particularly limited, for example, it is 60 to 250 by mass relative to the inorganic fiber nonwoven fabric.

[0073] The content of flame retardant in the fire-retardant material (the total amount when there are two or more flame retardants) is not particularly limited, for example, it is 0 to 150% by mass relative to the inorganic fiber nonwoven fabric. When the fire-retardant material contains flame retardant, the content of flame retardant in the fire-retardant material is preferably 15 to 150% by mass relative to the inorganic fiber nonwoven fabric.

[0074] Fire-retardant materials

[0075] The fire-retardant material disclosed herein comprises: an inorganic fiber nonwoven fabric; and a thickness inhibitor impregnated in the inorganic fiber nonwoven fabric.

[0076] The inorganic fiber nonwoven fabric of the fire-retardant material is restored to more than 60% of the thickness of the inorganic fiber nonwoven fabric before the thickness inhibitor was impregnated by the disappearance of the thickness inhibitor.

[0077] In order for the inorganic fiber nonwoven fabric to recover to the desired thickness when the thickness inhibitor disappears, it is necessary to maintain the resilience of the inorganic fiber nonwoven fabric by preventing the inorganic fibers from being crushed during recovery (i.e., preventing the inorganic fibers from being crushed during compression). If the inorganic fibers are crushed, they cannot maintain their fibrous state and will be in a pulverized state.

[0078] Even if a portion of the thickness inhibitor disappears, the fire-retardant material will recover as long as the binding of the thickness inhibitor to the inorganic fibers is released. Therefore, the disappearance can be complete or partial.

[0079] In a preferred embodiment, the disappearance of the thickness inhibitor means that the mass of the thermoplastic resin contained in the heated fire-retardant material is less than 60% of the mass of the thermoplastic resin contained in the fire-retardant material before heating.

[0080] The thickness of the fire-retardant material is preferably 0.50 mm to 15.0 mm, and more preferably 1.00 mm to 3.00 mm in order to be accommodated within the battery pack or between battery cells.

[0081] The thickness of the fire-retardant material can be measured, for example, by the measurement method shown in the following embodiments.

[0082] <Recovery Rate>

[0083] The ratio of the thickness of the fire-retardant material (or the inorganic fiber nonwoven fabric in the fire-retardant material, hereinafter the same) after the thickness inhibitor has disappeared to the thickness of the inorganic fiber nonwoven fabric before the thickness inhibitor was impregnated is called the recovery rate.

[0084] The recovery rate can also be easily determined by measuring the thickness of the inorganic fiber nonwoven fabric before impregnation with the thickness inhibitor and the thickness of other fire-retardant materials of the same type after the thickness inhibitor has disappeared, and calculating their ratio.

[0085] For example, in one embodiment, the thickness of the fire-retardant material after the thickness inhibitor disappears is the thickness of the fire-retardant material after heating it at 1000°C for 1 hour.

[0086] <GBD for Fire-Retardant Materials>

[0087] The GBD (compression density) of the fire-retardant material disclosed herein is not particularly limited, but if it is too high, there is a high possibility that the inorganic fibers of the fire-retardant material will be crushed during heating and recovery (i.e., the inorganic fibers of the inorganic fiber nonwoven fabric will be crushed during compression). Therefore, the GBD of the fire-retardant material is preferably 0.47 g / cm³. 3 The lower limit for GBD is not specifically defined, for example, it is 0.13 g / cm³. 3 above.

[0088] The GBD of fire-retardant materials is calculated by dividing the basis weight of the inorganic fiber nonwoven fabric by the thickness at compression.

[0089] In one embodiment, the thickness of the fire-retardant material after the thickness inhibitor disappears is at least 1.5 times the thickness before the thickness inhibitor disappeared. In another embodiment, the thickness of the fire-retardant material before the thickness inhibitor disappeared is 1.00 mm to 3.00 mm, and the thickness after the thickness inhibitor disappeared exceeds 3.00 mm, meaning the thickness after the thickness inhibitor disappeared is at least 1.5 times the thickness before the thickness inhibitor disappeared. This fire-retardant material possesses both mounting and thermal insulation properties and is suitable for use in battery cells.

[0090] In one embodiment of the fire-retardant material disclosed herein, a fire-resistant layer formed of an inorganic material may be laminated on at least one side of an inorganic fiber nonwoven fabric impregnated with a thickness inhibitor. The fire-resistant layer may be a particle impact-resistant layer as described in International Publication 2024 / 034628. By providing the fire-resistant layer, the fire-retardant performance (particularly particle impact resistance and fire resistance) is improved.

[0091] The refractory material layer can be integrated with the inorganic fiber nonwoven fabric by using a thickness inhibitor, or it can be bonded by adhesives.

[0092] Manufacturing method of fire-retardant materials

[0093] The method for manufacturing the fire-retardant material disclosed herein includes: an impregnation step in which a thickness inhibitor is impregnated in an inorganic fiber nonwoven fabric; and a curing step, which, after the impregnation step, maintains the thickness-inhibited state by cooling, drying, or chemically reacting the inorganic fiber nonwoven fabric impregnated with the thickness inhibitor. As described above, the inorganic fiber nonwoven fabric and the thickness inhibitor are not further elaborated upon.

[0094] As for methods of impregnating a thickness inhibitor into an inorganic fiber nonwoven fabric, there are no particular limitations as long as the method enables the impregnation of the thickness inhibitor into the inorganic fiber nonwoven fabric. Examples include: methods of permeating the inorganic fiber nonwoven fabric with a thickness inhibitor that has been melted by heating; methods of coating the inorganic fiber nonwoven fabric with a liquid containing a thickness inhibitor; and methods of injecting the inorganic fiber nonwoven fabric with a liquid containing a thickness inhibitor. The liquid containing the thickness inhibitor can be, for example, a solvent for dissolving the thickness inhibitor or a dispersion medium for dispersing the thickness inhibitor.

[0095] 1. Impregnation process

[0096] The impregnation process using a molten thickness inhibitor includes a heating stage and a pressurizing stage. The heating stage can be performed before or simultaneously with the pressurizing stage. It should be noted that there are no particular limitations on the heating temperature during the heating stage, as long as it exceeds the melting point of the thickness inhibitor. During the pressurizing stage, the inorganic fiber nonwoven fabric is pressurized, resulting in a state of compression in the thickness direction compared to the inorganic fiber nonwoven fabric before pressurization.

[0097] In one example, an inorganic fiber nonwoven fabric in contact with a solid thickness inhibitor (e.g., a sheet, film, powder, or granule containing a thermoplastic resin) is clamped in a mold. During a heating phase, the thickness inhibitor is melted, and in a subsequent pressurization phase, the molten thickness inhibitor is impregnated into the inorganic fiber nonwoven fabric. In another example, an inorganic fiber nonwoven fabric in contact with a solid thickness inhibitor (e.g., a sheet or film containing a thermoplastic resin) is clamped in a mold and heated under pressure, i.e., heating and pressurization are performed simultaneously, causing the molten thickness inhibitor to impregnate the inorganic fiber nonwoven fabric. During the impregnation process, the solid thickness inhibitor may contact only one side of the inorganic fiber nonwoven fabric, or it may contact both sides of the inorganic fiber nonwoven fabric. In this specification, "film" refers to a thin film with a thickness of less than 250 μm. "Sheet" refers to a plate-like component with a thickness of 250 μm or more. "Powder" refers to powder with a diameter of less than 1 mm. "Granule" refers to a granular component with a diameter of 1 mm or more.

[0098] 2. Curing process

[0099] In the curing process using molten thickness inhibitors, the molten thickness inhibitors are cured by cooling. There are no particular limitations on the cooling method, as long as it can cool the thickness inhibitor impregnated in the inorganic fiber nonwoven fabric; examples include air cooling, water cooling, and oil cooling.

[0100] The cooling temperature can be appropriately selected based on the cooling method and the type of thickness inhibitor, as long as it is the temperature at which the thickness inhibitor impregnated in the inorganic fiber nonwoven fabric solidifies. In the cooling process, the inorganic fiber nonwoven fabric is clamped in a mold, thereby maintaining its compressed state while cooling under specified conditions. The mold used in the cooling process can be the same as or different from the mold used in the impregnation process. Thus, the inorganic fiber nonwoven fabric is kept compressed in the thickness direction by the thickness inhibitor, thereby obtaining the fire-retardant material of this disclosure.

[0101] In the curing process using a solvent that dissolves the thickness inhibitor or a dispersion medium that disperses the thickness inhibitor, the inhibitor is cured by drying or chemical reaction of the solvent.

[0102] By selecting the thickness inhibitor impregnated in the inorganic fibers constituting the inorganic fiber nonwoven fabric, or the viscosity of the liquid containing the thickness inhibitor, the degree of compression of the inorganic fiber nonwoven fabric, etc., those skilled in the art can easily manufacture fire-retardant materials in which the thickness of the inorganic fiber nonwoven fabric is suppressed under normal conditions, and when the thickness inhibitor disappears, the inorganic fiber nonwoven fabric recovers to more than 60% of its thickness before impregnation with the thickness inhibitor.

[0103] In this embodiment, when cutting the inorganic fiber nonwoven fabric, the impregnation process can be performed before or after the cutting process. The cutting process can be performed before or after the curing process.

[0104] use

[0105] The fire-retardant material disclosed herein can be used in various applications, such as fire-retardant materials for battery packs. If a battery pack using the fire-retardant material disclosed herein is installed in electric vehicles, hybrid vehicles, electric motorcycles, ships, railways, and other electric transportation vehicles, even if the battery experiences thermal runaway and catches fire, its high thermal insulation properties can prevent the initial spread of the fire.

[0106] Figure 1 This is a perspective view of the sheet-like fire-retardant material 10 as an embodiment.

[0107] Figure 2 It includes a plurality of battery cells 20, a battery housing 30 that houses the plurality of battery cells 20, and a battery housing 30 therein. Figure 1 A cross-sectional view of the battery pack 100 with fire-retardant material 10. The battery casing 30 can also be called the outer shell. The battery cell 20 can be any type of cylindrical, square, or pouch cell, preferably a square type with high power density.

[0108] The fire-retardant material 10 can be disposed on the entire surface or a portion of the inner wall of the battery housing 30. For example, the battery housing 30 has an outer cover, i.e., an upper member 30a, and a lower member 30b, which is a receiving portion. The fire-retardant material 10 can be used by attaching it to the inner surface of the upper member 30a of the battery housing 30. In one embodiment, the fire-retardant material 10 is attached to the inner surface of the upper member 30a of the battery housing 30 at a certain interval relative to the battery cells 20. Even if a battery cell 20 experiences thermal runaway, the fire-retardant material 10 can suppress the transfer of heat to the upper member 30a of the battery housing 30. Therefore, it is possible to suppress fire from the battery housing 30, and when the battery pack 100 is mounted in a car or the like, it can protect the occupants from flames.

[0109] It should be noted that the flame-retardant material 10 can also be disposed between adjacent battery cells 20, for example. In one embodiment, the flame-retardant material 10 is disposed in contact with one or both of the adjacent battery cells 20. In order to suppress thermal runaway of the battery cell 20, a stacked structure in which the battery cell 20 is sandwiched between a pair of flame-retardant materials 10 can also be configured. Even if thermal runaway occurs in the battery cell 20, the transfer of heat to other adjacent battery cells 20 can be suppressed by the flame-retardant material 10.

[0110] The full disclosure of all patent applications and documents referenced in this specification is incorporated herein by reference.

[0111] The following examples are for illustrative purposes only and are not intended to limit the scope of the invention in any way. Unless otherwise specified, the reagents are commercially available or can be obtained or prepared according to conventional methods or procedures in the art.

[0112] Example

[0113] 1. Manufacturing of fire-retardant materials

[0114] Examples 1-4, Comparative Examples 1 and 3

[0115] On the mold, a resin film and a blanket made of nonwoven fabric of alumina / silica fibers (manufactured by Mafutek Co., Ltd., 600g / m²) are layered sequentially from bottom to top. 2PA6I film (polyamide resin film, 250mm × 250mm) was used to prepare a laminate, and a mold was placed above the laminate as a pressure plate. Next, the laminate, along with the mold, was placed on a hot and cold press and heated. After confirming that the mold had reached the specified temperature, pressure was applied from above to compress each laminate to a specified thickness (as an example, the target thickness during molding in Table 1). At this time, the amount of compression was managed by spacers to compress it to the specified thickness. After holding in the compressed state for 10 minutes, it was directly cooled to room temperature for about 20 minutes, and the compression-molded article was removed from the mold to complete the fire-retardant materials of Examples 1-4 and Comparative Examples 1 and 3.

[0116] Example 5

[0117] In the above-described manufacturing methods of the fire-retardant materials of Examples 1 to 4 and Comparative Example 1, a nonwoven fabric of alumina / silica fibers was used in the same way, and as a thickness inhibitor, granules (PNAH5, Novace Co., Ltd.) in which a non-halogen flame retardant was incorporated into polypropylene (PP) were used.

[0118] Comparative Example 2

[0119] Blankets made from nonwoven fabric of alumina / silica fibers (manufactured by Mafutek Co., Ltd., 432 g / m²) 2 A 300mm x 300mm blanket was impregnated in an alumina sol with a solid content concentration of 9.6% by mass, so that the alumina sol permeated the entire blanket. The blanket was clamped with a compression jig made of perforated metal and compressed to a specified thickness of 2.0mm, adjusted by spacers. The molded product was then placed directly into a dryer and dried at 120°C for 10 hours to complete the fire-retardant material of Comparative Example 2.

[0120] The thickness of the dried fire-retardant material is 2.38 mm, and the amount of inorganic binder is 76.1% by mass.

[0121] 2. Various experiments

[0122] (1) Determination of the thickness of the blanket before impregnation

[0123] First, the thickness of the blankets in Examples 1-5 and Comparative Examples 1-3 before impregnation was measured, and the thickness was calculated as the average of the measured values ​​at 6 randomly selected points in each blanket.

[0124] (2) Determination of the thickness of the fire-retardant material before resin removal

[0125] Next, the thickness of the fire-retardant material (100mm × 180mm) of each of Examples 1-5 and Comparative Examples 1-3 before resin removal was measured, i.e., the thickness of the molded article. This thickness was calculated as the average of the measured values ​​at 6 randomly selected points in each fire-retardant material.

[0126] (3) Determination of GBD

[0127] Next, the GBD (g / cm³) of each fire-retardant material in Examples 1-5 and Comparative Examples 1-3 was measured. 3 As described above, the GBD is calculated by dividing the basis weight of each blanket by its thickness at compression (the thickness of the fire-retardant material before resin removal).

[0128] (4) Mass ratio of thickness inhibitor to inorganic fiber mass

[0129] The mass ratio of the thickness inhibitor to the inorganic fiber is calculated by dividing the mass of the thickness inhibitor (the sum of the resin component and the flame retardant) by the mass of the inorganic fiber.

[0130] (5) Removal of resin components

[0131] Next, the fire-retardant materials of Examples 1-5 and Comparative Examples 1-2 were heated at 1000°C for 1 hour to remove the resin component. Then, the thickness of the fire-retardant material (100mm × 180mm) of Examples 1-5 and Comparative Examples 1-2 after the resin component was removed (after restoration) was measured. The calculation of this thickness was the same as that for the thickness measurement of the fire-retardant materials described above.

[0132] In addition, the condition of each fire-retardant material after resin removal was evaluated. Specifically, a qualitative evaluation was conducted on the presence or absence of pulverization of alumina / silica fibers and the presence or absence of warp yarns in the fire-retardant material after resin removal. The presence or absence of pulverization was evaluated by visual observation and by touching to determine whether the alumina / silica fibers crumbled. Regarding the presence or absence of warp yarns, the presence of visually identifiable warp yarns in the fire-retardant material after resin removal was evaluated as present, and the absence of visually identifiable warp yarns was evaluated as absent.

[0133] (6) Calculation of recovery rate

[0134] In addition, the ratio of the thickness (mm) of the fire-retardant material after resin removal to the thickness (mm) of the blanket before resin impregnation was used as the recovery rate (%).

[0135] (7) Thermal insulation evaluation test

[0136] Subsequently, the blanket is overlapped with a SUS plate (1.00 mm) with the blanket facing down, the center of the blanket is heated from below the blanket by a burner, and the heat insulation of the fire-resistant material after resin removal (after recovery) is evaluated. In the evaluation of heat insulation, if the temperature of the SUS plate is lower than 300°C after 5 minutes from the start of heating, it is regarded as acceptable; if it is higher than 300°C, it is regarded as unacceptable. Since the temperature benchmark for toxic gas generation from the coating agent of the battery pack is 300°C, the pass / fail benchmark for the heat insulation evaluation test is set at 300°C.

[0137] Furthermore, when heating with the burner, the temperature at the center of the upper SUS plate is measured ( Figure 3 ).

[0138] 3. Results and Investigation

[0139] The results are shown in Table 1.

[0140] In Examples 1 to 5 and Comparative Examples 1 to 2, the thickness of the fire-resistant material before resin removal is controlled within ±0.5mm relative to the target thickness during molding, which falls within the highly mountable thickness range of 1.00mm to 3.00mm. On the other hand, for the fire-resistant material of Comparative Example 3, since the mass ratio of the thickness inhibitor relative to the mass of inorganic fibers is low, the thickness is 3.35mm relative to the target molding thickness of 2mm, which indicates insufficient thickness inhibition and fails to achieve the desired mountability.

[0141] Furthermore, in the state after resin removal of the fire-resistant materials of Examples 1 to 5, the resin component disappears, but the alumina / silica fibers are not pulverized and the warp yarns are retained, which indicates that the structure and function of the fire-resistant material are maintained. As a result, the recovery rates of the fire-resistant materials of Examples 1, 2, 3, 4, and 5 are 69%, 87%, 88%, 88%, and 80%, respectively. On the other hand, in the fire-resistant material of Comparative Example 1, the alumina / silica fibers are pulverized, and there are no warp yarns left, which indicates that the structure and function of the fire-resistant material are degraded. As a result, the recovery rate of the fire-resistant material of Comparative Example 1 is 59%. Although the alumina / silica fibers in the fire-resistant material of Comparative Example 2 are not pulverized, the alumina sol (inorganic binder) maintains the binding of the alumina / silica fibers, leading to a low recovery rate.

[0142] The fire-resistant materials of Examples 1 to 5, which maintain the structure and function of the fire-resistant material, have a higher recovery rate compared with the fire-resistant materials of Comparative Examples 1 and 2.

[0143] As Figure 4As shown, it was confirmed that when using the fire-retardant materials of Examples 1 to 4, the temperature of the SUS board remained below 300°C even 5 minutes after heating with a burner, exhibiting higher heat insulation performance compared to the fire-retardant sheet of Comparative Example 2. It should be noted that the fire-retardant sheet of Comparative Example 1 could not overlap with the SUS board because the alumina / silica fibers had pulverized.

[0144]

[0145] Symbol Explanation

[0146] 10: Fire-retardant material; 20: Battery cell; 30: Battery casing; 100: Battery pack.

Claims

1. A fire-retardant material, said fire-retardant material comprising: Inorganic fiber nonwoven fabric; and Thickness inhibitor, impregnated in the inorganic fiber nonwoven fabric; The inorganic fiber nonwoven fabric is kept in a compressed state in the thickness direction by the thickness inhibitor. The inorganic fiber nonwoven fabric recovers to more than 60% of its original thickness before the thickness inhibitor was impregnated upon the disappearance of the thickness inhibitor.

2. The fire-retardant material according to claim 1, wherein, The inorganic fiber nonwoven fabric is a needle-punched blanket containing alumina / silica fibers.

3. The fire-retardant material according to claim 1, wherein, The thickness inhibitor comprises a thermoplastic resin.

4. The fire-retardant material according to claim 3, wherein, The thickness inhibitor contains a flame retardant.

5. The fire-retardant material according to claim 1, wherein, The basis weight of the inorganic fiber nonwoven fabric is between 400 and 1400 g / m². 2 Within the range.

6. The fire-retardant material according to claim 1, wherein, The GBD of the inorganic fiber nonwoven fabric under compression is 0.47 g / cm³. 3 the following.

7. A battery pack comprising: a plurality of battery cells; a battery housing for accommodating the plurality of battery cells; and a fire-retardant material according to any one of claims 1 to 6, accommodating within the battery housing.

Citation Information

Patent Citations

  • Inorganic fiber composite material, battery pack cover, battery pack, and electric-powered mobility

    WO2024034628A1

  • Laminate

    WO2024085233A1